Rising from the ashes: resurrection of the Malagasy chameleons Furcifer monoceras and F. voeltzkowi (Squamata: Chamaeleonidae), based on micro-CT scans and external morphology - Sentís, Marina; Chang, Yiyin; Scherz, Mark D.; Prötzel, David; Glaw, Frank (Zootaxa, 2018)
The taxonomy of the Malagasy chameleon Furcifer rhinoceratus (Gray, 1845) is poorly resolved. The aim of this study is to clarify the taxonomic status of Chamaeleon voeltzkowi Boettger, 1893 and Chamaeleon monoceras Boettger, 1913 both only known from single or very few specimens mostly collected more than 100 years ago and currently considered as synonyms of Furcifer rhinoceratus. Using osteological data from micro-X-ray computed tomography (micro-CT) combined with traditional morphological characters and morphometrics we resurrect both taxa from the synonymy of F. rhinoceratus as F. voeltzkowi and F. monoceras, respectively. Compared to F. rhinoceratus, F. monoceras is smaller, has a relatively shorter tail, a longer and thinner rostral appendage, a poorly developed gular crest and no ventral crest, whereas F. voeltzkowi has a smaller rostral appendage, higher casque and the dorsal crest is continuous with the tail crest. Compared to the broad rostral appendage formed by the anterior protuberance of the premaxillary process of the maxilla, which has serrated edges in F. rhinoceratus, F. monoceras presents a long rostral appendage with a smooth dorsal edge that progressively narrows, and the nasal aperture is extended along the elongated appendage; F. voeltzkowi presents a smaller but curved rostral appendage with a crenate edge. The prefrontal and postorbitofrontal approach one another forming a large, laterally closed supraorbital fontanelle in F. rhinoceratus while in F. monoceras they do not approach, leaving a laterally open fontanelle, and in F. voeltzkowi the fontanelle is diminutive. Furcifer voeltzkowi also differs from the similar F. labordi by a smaller size of the rostral appendage, less bulging casque and body pholidosis. The former exhibits a conspicuous white lateral band comprising heterogeneous scalation. Furcifer labordi, on the other hand, has a homogeneous scalation with a remarkable reticulate pattern. Osteologically, the shape of the prefrontal and the connection of the postorbitofrontal with the parietal also differ greatly between the two. Using micro-CT scans we detected key differences that would be otherwise impossible to determine. We also provide a brief morphological and osteological description of the species and strongly recommend efforts to rediscover these two poorly known taxa in order to enable additional studies and to assess their conservation status.